Stock de carbono en suelos antrópicos de bosques secundarios en la amazonia central brasilera - Oblitas Mendoza, Erick Manuel (2021)
In the Brazilian central Amazon, there are anthropic soils popularly known in the native language as “Terra Preta de Indio” (Dark earth) that present a dark colored soil profile that generally presents high natural fertility as a characteristic, with high concentrations of P, Ca, Mg, Zn and organic matter. As in general, they present high levels of C, with concentrations up to 150 g C kg¯1, the capacity of anthropic soils to store C is stable at high levels, being an important mechanism to reduce the “greenhouse effect” that needs to be further evaluated and understood. This study has the objective to determine the stock of C in the anthropic and adjacent soils under secondary forests of the central Brazilian Amazon. From where we opened pit and collected undisturbed samples of the three types of soils studied, where we analyzed the concentrations of C with which we calculated the Stokes of C, as well as the physical and chemical properties of these soils. Hence, we found that the TPI in the EA area has a greater stock of C than SA, with values of 204.9 and 176.5 Mg C ha-1 respectively, but there is no significant difference. The Stokes are smaller in the other TPIs in other areas. For which we conclude that the greater stock of C found in the SA is due to the difference that it has in its concentration of clay, being greater when compared to the TPI. The concentration of clay in the soil is related to the concentration of C in the soil.